Issues and Protection of Mobile Application Security - Rosy, M. Angelin; Shilpa, N; Muthu, M. Felix Xavier (International Journal of Computer Sciences and Engineering, 2025)
Now a days, people give more important to the smartphones. Smartphone users are increasing day by day. Mobile device contains sensible data and hackers easily access our data. Avoid installing more free apps and cyber criminals to avoid cyber crime. All the vulnerabilities are increasing by the hackers. Use block option in some applications to block the camera. Use pin code, patterns, finger prints and iris scanner to secure Smartphone applications. Android platform will be made available under apache software and open source licence. To avoid cyber crime use antivirus software and firewalls keep them to update. Don’t open email or attachment from unknown sources.